Serum levels of antioxidants and its supplementation in people living with HIV: integrative review - Aline Roberta Rodrigues da Silva; Patricia Dias de Brito (Hospital de Clínicas de Itajubá, 2021)
Objective: To conduct an integrative review of serum levels of antioxidants and the effects of their supplementation on people living with HIV (PLHIV). Methods: A research was performed in the electronic databases LILACS and MEDLINE, using the descriptors "HIV" AND "antioxidants"; 110 publications were identified, 92 of which were available in the MEDLINE database and 3 in the LILACS database. After applying the exclusion criteria, 8 articles were selected for final evaluation.Results: The studies selected for the review were divided into 4 prospective observational studies and 4 clinical trials with supplementation of antioxidants or food sources of antioxidants. We observed that the initiation of antiretroviral therapy and its prolonged use negatively influenced the parameters of oxidative stress, and that deficiency of antioxidants was associated with more significant damage to mitochondrial DNA. Supplementation of foods that are sources of antioxidants, such as dark chocolate and spirulina, has had beneficial effects on serum lipids and antioxidant capacity. Conclusion: Clinical trials with a more robust methodology, supplementation of isolated nutrients, for more extended periods of intervention, and with the assessment of food consumption are necessary to elucidate their effects on oxidative stress in PLHIV faced with factors such as the use of antiretroviral therapy and changes in metabolic rates of this population.